Methods in scientific and religious inquiry - Rolston, Holmes, 1932-2025, author; Random House, publisher (Colorado State University. Libraries, 1987)
In generic logical form science and religion are more alike than is often supposed, especially at their cores. At the same time, science and religion typically offer alternative interpretations of experience, the scientific interpretation being based on causality, the religious interpretation based on meaning. But both disciplines are rational, and both are susceptible to improvement over the centuries; both use governing theoretical paradigms as they confront experience. The conflicts between scientific and religious interpretations arise because the boundary between causality and meaning is semipermeable.
Keywords: interpretations; methodology; science; religion; theory; paradigms; verification